Fig. 21 in Cambrian microfossils from glacial erratics of King George Island, Antarctica ... - Wrona, Ryszard (Zenodo, 2004)
Fig. 21. Sclerite of Hadimopanella staurata sp. nov., ZPAL V.VI/24S24, errratic boulder Me40. A. Oblique lateral view. B. Upper view. C, D. Enlargements of B showing arrangement of phosphate crystallites in the external layer. ... : Published as part of Wrona, Ryszard, 2004, Cambrian microfossils from glacial erratics of King George Island, Antarctica, pp. 13-56 in Acta Palaeontologica Polonica 49 (1) on page 45, DOI: 10.5281/zenodo.13285795 ...